Physiological and mechanical responses to a graded exercise test in traditional rowing - Penichet-Tomas, A.; Jimenez-Olmedo, J. M.; Pueo, B.; Olaya-Cuartero, J. (International Journal of Environmental Research and Public Health, 2023)
Maximum oxygen consumption and maximum power output are critical measures for training prescription in endurance sports such as rowing. The objective of this investigation was twofold: to compare the physiological and mechanical responses of female and male traditional rowers during a graded exercise test and to establish reference values in this specific rowing modality that have not yet been documented, unlike in Olympic rowing. Twenty-one highly trained/national level rowers participated in the study: 11 female (age: 30.1 ± 10.6 years, height: 167.3 ± 5.0 cm, body mass: 61.9 ± 4.9 kg) and 10 males (age: 33.5 ± 6.6 years, height: 180.8 ± 6.9 cm, body mass: 74.4 ± 6.9 kg). Significant differences (p < 0.05) were found in rowing performance between sexes, with a very large effect size (d = 7.2). The peak power output for the female rowers was 180.9 ± 11.4 W and 287.0 ± 17.7 W for the male rowers. The female rowers reached a VO2max of 51.2 ± 6.6 mL/kg/min at a mean of 174.5 ± 12.9 W, while the males` VO2max was 62.1 ± 4.7 mL/kg/min at a mean of 280.0 ± 20.5 W. These differences in VO2max and maximal aerobic capacity were significant (p < 0.05), with a large (d = 1.9) and very large (d = 6.2) effect size, respectively. A moderate association between VO2max, and rowing performance expressed in watts per kilogram of muscle mass was observed in the female rowers (r = 0.40, p = 0.228). For the male rowers, the correlation between VO2max and relative peak power output in watts per kilogram of body mass was strong (r = 0.68; p = 0.031). This study highlights the differences in the kinetics of ventilatory and mechanical parameters between female and male rowers and the importance of these differences for specific physical preparation in traditional rowing.